1354. Incidence, time trends and geographic distribution of Lyme neuroborreliosis in Denmark using public surveillance data, 2015-2019. (15th December 2022) - Skufca, Jozica; DeSmedt, Nick; Pilz, Andreas; Vyse, Andrew; Begier, Elizabeth; Blum, Maxim; Riera, Margarita; Gessner, Bradford; Skovdal, Mette; Stark, James
Abstract: Background: Lyme neuroborreliosis (LNB) is a potentially severe manifestation of Lyme borreliosis (LB), a spirochetal tick-borne infectious disease caused by Borrelia burgdorferi . We describe the incidence, time trends and geographic distribution of LNB in Denmark, with the aim to inform public health policy, including the potential use of new vaccines under development. Methods: Based on the case definition for LNB (clinical diagnosis of LB plus detection of antibodies in blood and cerebral spinal fluid [confirmed case], OR clinical symptoms compatible with LNB and detection of antibodies in blood [probable case]), we obtained cases reported by laboratories and physicians (2015–2019) from the online platform maintained by the Statens Serum Institut (SSI). The LNB incidence (per 100, 000 persons) was calculated by dividing LNB cases by the population data (denominator) obtained from Statistics Denmark. Results: Between 2015 and 2019, laboratories reported annually 162 to 200 LNB cases, while physicians reported 48 to 68 cases (Figure). The annual LNB incidence notified by laboratories ranged from 2.8 (95% CI: 2.4‒3.3) to 3.4 (95% CI: 3.0‒4.0) per 100, 000 persons for the 5 study years. The average annual LNB incidence per 100, 000 persons for 5 Danish regions ranged from 2.3 to 3.3; for 11 provinces, from 1.9 to 7.6; and for 98 municipalities, from 0 to 22.1. Incidence peaks occurred in persons 5‒14 and 65‒74 years of age. Higher incidences were observed among males versus females in all age groups. LNB cases were reported throughout the year, with peaks in July to September. Number of LNB cases and annual incidence (per 100, 000 population) notified by (A)physicians and (B) laboratories Conclusion: LNB incidence in Denmark is moderate with no evidence of decline. Cases occurred across all regions but were focally concentrated among residents of some municipalities. By analyzing and reporting spatially granular data, we could identify areas with the highest LNB incidence. This may assist policy makers with assessing the efficiency of geographically targeted versus national prevention interventions, including vaccines should these be licensed. To this end, expanding the current surveillance system to include other manifestations of LB would be valuable to better understand geographic endemicity. Disclosures: Jozica Skufca, Epidemiologist, p95: Paid by Pfizer to perform the study Nick DeSmedt, Masters in Computer Engineering, P95: P95 was paid by Pfizer to perform the study Andreas Pilz, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds|Pfizer: Stocks/Bonds Andrew Vyse, Ph.D., Pfizer: Stocks/Bonds Elizabeth Begier, M.D., M.P.H., Pfizer: Employee|Pfizer: Stocks/Bonds Maxim Blum, Ph.D., P95: Paid by Pfizer to perform the study Margarita Riera, MD, MPH, P95: Paid by Pfizer to perform the study Bradford Gessner, MD, MPH, Pfizer: Stocks/Bonds Mette Skovdal, Ph.D., Pfizer Denmark: Stocks/Bonds James Stark, Ph.D., Pfizer: Stocks/Bonds.